The homeless diaspora of queer Asian Americans - Otalvaro-Hormillosa, Sonia (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer discusses the homeless diaspora of homosexual Asian-Americans. She investigates the problems in conceptualizing hybridity in terms of homosexual diaspora as a result of unequal power relationships that exist between members of the same diaspora, some of whom enjoy more economic privileges. She examines the extent to which the boundaries of specific diasporas are changeable and can overlap with other diasporas to form a multiple, but homeless, diasporic consciousness. She concludes that for migrant homosexuals, the notion of transnationalism acquires a hybrid performativity that becomes a function of homosexual diaspora and a vital part of activism and organizing across borders.